The Imaginative Ethnographer as Vagabond Bricoleur: Being Still, Being Quiet, Standing in Love and Paying Attention: An Interview with Magdalena Kazubowski-Houston and Virginie Magnat - Soyini, Madison D. (Anthropologica, 2018)
This interview discusses the infinity of stories as an endless reservoir of imagining new forms of meaning, feeling and embodiment of fieldwork data. Thinking of ethnographic analysis and experience as a collaborative process of performance and creative expression is an alternative to the prevailing textocentric documentation that demands both a political economy of contexts and an ethics of loving attention.